BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PENERIMAAN JAMAAH UMRAH TERHADAP VAKSIN MENINGITIS DI KANTOR KESEHATAN PELABUHAN KELAS II SEMARANG - Syara Octaviana Hafshoh; Syamsulhuda BM; Besar Tirto Husodo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Meningococcal vaccine is a vaccine that must be given to everyone who will to Saudi Arabia. This vaccine began to be required in 2006 because of an outbreak of meningococcal disease in Saudi Arabia from the span of 1987-2003 and the disease infected hajj pilgrims. 44 out of 747 umrah pilgrims are late to get vaccine eventhough this vaccine must be given no later than 14 days before the departure of hajj or umrah. Because this vaccine will work 14 days after the pilgrims got vaccinated. This study aims to analyze the factors associated with the acceptance of umrah pilgrims to meningitis vaccine. This research is a mix methods study with descriptive-analytics method and uses accidental sampling technique. The data is collected using questionnaire with interview method.The results shows that 23% of the umrah pilgrims were late of getting meningococcal vaccine. The chi-square test shows that the knowledge about meningococcal vaccine (p=0.04, perceived susceptibility (p=0.025), perceived benefit (p=0.01) and environmental support (p=0.035) are significantly associated with the acceptance of meningococcal vaccine. While gender (p=0.827), age (p=0.188), education (p=0.827), perceived severity (p=0.797), perceived barrier (p=0.101), and family support (p=0.440) are not significantly associated with the acceptance of meningococcal vaccine.